Inductance simulator with electronic controllability using single VDDDA - Pichetpaisan, Kunakom; Jaikla, Winai; Siripongdee, Surapong; Adhan, Suchin; Silapan, Phamom (My University, 2019)
This research paper presents an active inductance simulator utilizing single voltage differencing differential difference amplifier (VDDDA), single grounded capacitor and single resistor. The control of inductance value is electronically done via adjusting bias current of VDDDA which is attractive for controlling by the microcontroller or microprocessor. To investigate the functionality of the presented active inductance simulator, the voltage-mode biquadratic band reject is designed. The theoretical behaviors of the proposed active inductor and its application are verified via Pspice simulation program and experiment using VDDDA constructed from the commercially available ICs.
Keywords: Biquadfilter.; Inductance simulator; VDDDA